Impacto del corte manual y su relación con enfermedades profesionales en trabajadores de corte en Provefrut. Elaboración de un sistema de gestión. - Uribe Campaña, Víctor Hugo (2015)
The objective of this work was the elaboration of an Occupational Health Management System for Court Area of the Provefrut Agroindustrial. For that a situational analysis was done in which the incidence of musculoskeletal disorders was evidenced that affect to workers and that in several cases have ended in an occupational disease. Through using statistical methods and the application of a test to identify early symptoms, the symptomatic was known in the cutting area becoming more than 65%. The test was designed with the purpose to collect the symptoms of upper limb that suffers affection by the repetitive movements in manual cutting. The management system was designed in base protocols of the main operations to provide a tool for controlling the disergonomic risk factor. The elaboration of the Occupational Health Management System for the Court Area allows improving the workers’ life quality. Therefore it concludes that the system is a basic tool for all types of organization that seeks to improve the quality and continuous improvement. The implementation of the Occupational Health Management System for Court area in Provefrut is recommended.